Rasio Pembiayaan Bermasalah, Tingkat Kecukupan Modal, Dan Rasio Profitabilitas Di PT. Bank Muamalat - Irma Novida (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2016)
In obtaining profit or banking profitability is not separated from the name of risk, because it cannot be denied that in fact the banking industry is an industry that is closely related to the risk, especially since it involves the management of public money and played in the form of investment activities, such as credit or financing. Financing is one form of business of the bank as an indicator in the assessment of the bank, for financing the assets which provide the largest portion of income for banks. Financing risks will have an impact on the smooth and banks ability to obtain profitability. In addition, many financial problems can lead to the erosion of bank capital that can be seen from the Capital Adequacy Ratio (CAR). The decrease of CAR certainly result in decreased ability of banks to channel financing, which in the end the bank to lose its ability to generate optimal profit. In addition, banks may have difficulties endangering its survival is characterized by decreasing capital, asset quality, liquidity and profitability as well as bank management is not carried out based on the precautionary principle and the principles of sound banking.